The birchbark house - Erdrich, Louise (New York : Hyperion Books for Children, 2002)
Omakayas, a seven-year-old Native American girl of the Ojibwa tribe, lives through the joys of summer and the perils of winter on an island in Lake Superior in 1847.
Accelerated Reader AR
Keywords: Ojibwa Indians -- Juvenile fiction; Indians of North America -- Fiction; Islands -- Fiction; Seasons -- Fiction; Ojibwa Indians -- Fiction